2001
DOI: 10.1053/euhj.2000.2482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asynchronous ventricular activation on myocardial adrenergic innervation in patients with permanent dual-chamber pacemakers. An I123-metaiodobenzylguanidine cardiac scintigraphic study

Abstract: Stimulation from the apex of the right ventricle leads to regional disturbances of the adrenergic innervation of the left ventricular myocardium, as assessed by I(123)-MIBG activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 37 publications
3
17
1
2
Order By: Relevance
“…При стимуля-ции верхушки ПЖ наблюдалось снижение ударного объ-ема по сравнению со стимуляцией правого предсердия [25]. Описанные изменения сократимости в областях наиболее ранней электрической активации миокарда приводят к нарушению адренергической иннервации [18,26], уменьшению метаболических потребностей [46], сни-жению потребления кислорода, фиброзу и истончению миокарда [12].…”
Section: патогенез неблагоприятных последствий апикальной пж-стимуляцииunclassified
See 1 more Smart Citation
“…При стимуля-ции верхушки ПЖ наблюдалось снижение ударного объ-ема по сравнению со стимуляцией правого предсердия [25]. Описанные изменения сократимости в областях наиболее ранней электрической активации миокарда приводят к нарушению адренергической иннервации [18,26], уменьшению метаболических потребностей [46], сни-жению потребления кислорода, фиброзу и истончению миокарда [12].…”
Section: патогенез неблагоприятных последствий апикальной пж-стимуляцииunclassified
“…Наиболее вероятно, что нарушения перфузии обу-словлены перераспределением коронарного кровотока вследствие ауторегуляции сосудистого тонуса из-за раз-ницы преднагрузки на различные участки миокарда [1, 8,27]. Другими возможными механизмами могут являться вазоконстрикция вследствие повышения тканевого нор-эпинефрина в зоне стимуляции [18,26] и поражение ми-кроциркуляторного русла за счет фиброзно-дегенератив-ных процессов [12]. Дефекты перфузии могут сочетаться с нарушениями локальной сократимости в соответствую-щих зонах, которые невозможно отличить от рубцового поражения миокарда вследствие перенесенного инфаркта [36].…”
Section: патогенез неблагоприятных последствий апикальной пж-стимуляцииunclassified
“…Pathomechanisms of Chronic--Stimulated Heart Failure Abnormal Blood and Adrenergic Myocardial Perfusion E. N. Simantirakis et al [19] showed that RVA stimulation, besides blood perfusion disorders in the area of stimulation, also causes disturbances in adrenergic conduction system. This data proves the theory of correlation between the specific place of stimulation and its adequate effect on electrical impulse conduction system and regional blood perfusion.…”
Section: Left Atrium and Mitral Valve Dysfunction -Atrial Fibrillationmentioning
confidence: 99%
“…6 On the other side, in patients with dual-chamber pacemaker it was observed that stimulation from the apex of the right ventricle is responsible for regional alteration of the adrenergic innervation of the left ventricular myocardium, as assessed by I(123)-MIBG activity. 7 Magnetic resonance imaging (MRI) has also been used to assess ventricular asynchrony and its response to pacing therapy. 8,9 In patients with non-ischemic heart failure, spatial dyssynchrony, as assessed by cross-correlation analysis of time curves of myocardial circumferential strains delivered from cine-tagging MRI images, was correlated with an impairment of cardiac sympathetic activity.…”
mentioning
confidence: 99%